Tissue-Specific GHR Knockout Mice: Metabolic Phenotypes - Sun, Liou Y.; Bartke, Andrzej (Frontiers in Endocrinology, 2015)
In addition to its major role in the regulation of somatic growth, GH signaling has profound effects on function of various tissues in the body. However, the cellular location where the GH signaling exerts its effect on metabolic homeostasis remains largely unknown. Here, we briefly review recent progress and insights from mice with GH receptor deletion specifically in adipocytes, macrophages, hepatocytes, pancreatic β-cells and skeletal muscle cell types. These studies have greatly enhanced our understanding of the GH-IGF-I physiological function.